Analisis Pola Fungsi Kalimat pada Teks Berita Daring CNN Nasional Edisi Januari 2024 sebagai Sumber Bacaan Siswa Kelas XI SMA - Ivana Zafirah; Lu’Lu’ Nur Fadiya; Asiah Khairunnisa Azzahra; Windi Elika Sari; Rizki Ayudika Yulistiani; Asep Purwo Yudi Utomo; Oktarina Puspita Wardani (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
The existence of online news in the midst of students can be considered as a source of easy information acquisition. Not only as information acquisition but also as a chapter of material used as learning material for grade XI high school students. The selection of news texts for students should be considered as a source of reading. The purpose of this study is to determine the effectiveness of sentence function patterns in CNN online news texts as a reading source for grade XI high school students. This research article uses a theoretical approach, namely a syntactic approach by analyzing the types and forms of sentence patterns. As for this research, the qualitative descriptive method is used to analyze related data. The researcher performs listening and recording techniques on CNN online news text to understand the content contained in the news text, then the researcher records the analysis of single sentence patterns and compound sentences contained in the news text using the agih method. From the data analysis that has been done, it was found that there are 49 single sentences and 33 compound sentences in CNN news whose sentence function patterns are simple and easy to understand for reading sources for high school grade XI students. The results of the analysis in this article are expected to add a deeper understanding and knowledge about the types and patterns of sentence functions and their feasibility to be used as a reading resource for students of grade XI SMA. Sentence patterns and their usage as well as knowledge about their types can be used as a reading resource for students.